Die Baltischen handels-beziehungen mit Russland: Pfadabhängigkeiten trotz EU-Integration? Challenging the Baltic states trade relations with Russia: caught in path dependencies? - Schrader, Klaus; Laaser, Claus-Friedrich (Estonian Discussions on Economic Policy, 2015)
Against the backdrop of the lingering Ukraine crisis, Russia retaliated against the EU sanctions imposed on selected Russian enterprises and representatives by boycotting import goods from European and North American suppliers. Russian politicians further threatened to restrict the export of raw materials, especially natural gas, provided that the EU-Russia relations further worsen and sanctions gather momen-tum. Hence, the paper deals with the question to what extent the EU economies Estonia, Latvia and Lithuania are vulnerable to Russian reprisals and would experience comparatively high costs of the EU sanction policy. The focus of the analysis is on the Baltic States’ trade relations with Russia because these countries were integrated in the Soviet division of labor before regaining independence. It is analyzed whether path dependencies in Baltic trade patterns still exist that could make Estonia, Latvia and Lithuania more vulnerable to political blackmail than other EU countries.